Extraction and application of essential oils from feijoa as a preservative in the production of fine dough sausages - Arteaga Peñafiel, Marina Urbeci; Briones Córdova, María; Velásquez Pionce, Peter (Ingeniería Química y Desarrollo, 2023)
In the present work, the extraction of essential oils from feijoa (Acca Sellowiana) is proposed to be applied in the elaboration of a fine paste sausage as a substitute for chemical additives, such as nitrites, looking for an option free of side effects. Within our research through various bibliographical sources, we found important data about the origin of feijoa, varieties, different applications, nutritional composition and a highlighted antioxidant capacity; as well as the sausages of fine pasta, its history, ingredients and preparation methods. With this information, we perform the respective laboratory tests described in the different stages of experimentation of this work were carried out. From the extraction of the essential oils, to, the different formulations of mortals using a variable percentage of oils in each sample to be evaluated, hedonic classification tests were also carried out with the presence of 70 judges and finally tests of estimation of useful life, both in controlled environment (refrigeration at an estimated temperature between 0 - 4 ° C) and in an uncontrolled environment (variable temperature and humidity of the city of Guayaquil). Among the results obtained through the tests carried out on the different samples of the mortise type sausage which were subjected to various formulations, using different percentages of the essential oils described above, it was concluded that, of these samples, one, achieved an acceptability of 31.82 %, both in the case of hedonic tests, as well as in laboratory tests. The formulation prepared for the same verifies that it is a type I bologna and meets all the requirements of NTE standards INEN 1529-5, 1529-8, 1529-14 and 1529-15 thus confirming the complete safety of the product, finally, in the tests of estimation of useful life, it was possible to confirm that feijoa oils, fulfill the function of preservative in sausages of fine pasta, by comparison with other products of the same class, but with a heterogeneous chemical formulation to that described in our work
Keywords: Feijoa; Essential oils; Sausages; Mortadella; Preservative